Low-Rank Sum-of-Squares Representations on Varieties of Minimal Degree. (18th June 2017) - Blekherman, Grigoriy; Plaumann, Daniel; Sinn, Rainer; Vinzant, Cynthia
Abstract: A celebrated result by Hilbert says that every real nonnegative ternary quartic is a sum of three squares. We show more generally that every nonnegative quadratic form on a real projective variety X of minimal degree is a sum of (X)+1 squares of linear forms. This strengthens one direction of a recent result due to Blekherman, Smith, and Velasco. Our upper bound is the best possible, and it implies the existence of low-rank factorizations of positive semidefinite bivariate matrix polynomials and representations of biforms as sums of few squares. We determine the number of equivalence classes of sum-of-squares representations of general quadratic forms on surfaces of minimal degree, generalizing the count for ternary quartics by Powers, Reznick, Scheiderer, and Sottile.